2011
DOI: 10.3102/0034654311403323
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Induction and Mentoring Programs for Beginning Teachers

Abstract: This review critically examines 15 empirical studies, conducted since the mid 1980s, on the effects of support, guidance, and orientation programs-collectively known as induction -for beginning teachers. Most of the studies reviewed provide empirical support for the claim that support and assistance for beginning teachers have a positive impact on three sets of outcomes: teacher commitment and retention, teacher classroom instructional practices, and student achievement. Of the studies on commitment and retent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
777
2
94

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 992 publications
(895 citation statements)
references
References 37 publications
22
777
2
94
Order By: Relevance
“…In turn, this should improve their effectiveness as teachers, resulting in higher student achievement, and decrease the turnover-related turbulence faced by students, because their teachers are less likely to leave. Ingersoll and Strong (2011) critically reviewed the research on these programs. They screened the literature and selected 15 empirical studies.…”
Section: Teacher Retention and School Attributesmentioning
confidence: 99%
“…In turn, this should improve their effectiveness as teachers, resulting in higher student achievement, and decrease the turnover-related turbulence faced by students, because their teachers are less likely to leave. Ingersoll and Strong (2011) critically reviewed the research on these programs. They screened the literature and selected 15 empirical studies.…”
Section: Teacher Retention and School Attributesmentioning
confidence: 99%
“…dans cette perspective, les autorités scolaires ont le mandat d'organiser régulièrement des activités d'intégration des nouveaux et de formation continue des anciens au sein du milieu de travail (alhija & Fresko, 2010 ;reynolds, ross, & rakow, 2002 ;reynolds & wang, 2005). en particulier, le mentorat s'avère être un outil efficace pour entretenir un climat organisationnel favorable à l'insertion professionnelle, au développement professionnel aussi bien des débutants que des plus expérimentés, à la collaboration, au soutien des autorités scolaires, à la construction de l'identité professionnelle et à la rétention des enseignants (devos, Mouton, & Marigliano, 2013 ;duchesne & Kane, 2010 ;Gardner, 2010 ;ingersoll & strong, 2011 ;Martineau & vallerand, 2006 ;Mukamurera, Martineau, Bouthiette, & ndoreraho, 2013). comme l'union fait la force, il faut instaurer une culture favorisant la création des alliances professionnelles entre les nouveaux et les anciens enseignants pour que l'expérience des uns soit une source d'inspiration pour les autres (cherubini, 2009).…”
Section: Discussion Et Conclusionunclassified
“…Research suggests that coaching is an effective way to support the learning of beginning teachers (Ingersoll & Strong, 2011). Darling-Hammond (1997 suggested that the research supports that quality induction programs pay for themselves with reduced teacher attrition and improved student learning.…”
Section: Induction Coachingmentioning
confidence: 99%
“…shown that specific components are needed for an induction coaching program to be successful (Ingersoll & Strong, 2011). In order to be effective, a trained induction coach must spend extensive time in the beginning teacher's classroom, embedded in the school culture (Ingersoll & Strong, 2011).…”
Section: Induction Coachingmentioning
confidence: 99%
See 1 more Smart Citation